Subnational Capacities Strengthened by REDD+ Himalaya Project in the Districts of Nepal - Chand, Jagriti; Windhorst, Kai; Poudel, Mohan; Bhattarai, Nabin (Journal of Forest and Livelihood, 2018)
The wellbeing of the forest dependent population relies upon the capacities of actors working at the ground level. It is crucial to assure that the capacity of these ground level actors is built for the effective implementation and success of any project. In this context, Reducing Emissions from Deforestation and Forest Degradation (REDD+) Himalaya project has been one of the key initiatives for REDD+ capacity building in the three project districts (Gorkha, Chitwan and Dolkha) of Nepal. The paper compiles available evidence illustrating REDD+ Himalaya’s role in capacitating the REDD Subnational and Local actors to support the REDD+ readiness process. Required data was collected from available project reports and interview with the sub-national and local actors working in the project districts. This study found that the REDD+ Himalaya project has strengthened local capacity to deal with REDD+, climate change and community forestry related issues. Major activities implemented in the project districts were capacity building related such as trainings, consultations, meetings, workshops, exposure visits and knowledge dissemination through mass media. The project applied three basic approaches (micro, meso and macro) for capacity building activities. Hence, it strengthened capacity of stakeholders with diverse interests, level and capacities including individuals (ranging from policy to local level), interest groups (forest officers, forest users, women, indigenous people, marginalized groups and elected members of the local governments) and related institutions (REDD IC, DFOs, CFUGs, FECOFUN and NEFIN).